Congenital hyperinsulinism and mosaic abnormalities of the ploidy. Issue 3 (20th July 2005) - Giurgea, I; Sanlaville, D; Fournet, J-C; Sempoux, C; Bellanné-Chantelot, C; Touati, G; Hubert, L; Groos, M-S; Brunelle, F; Rahier, J; Henquin, J-C; Dunne, M J; et al.
Abstract : Background: Congenital hyperinsulinism and Beckwith-Wiedemann syndrome both lead to β islet hyperplasia and neonatal hypoglycaemia. They may be related to complex genetic/epigenetic abnormalities of the imprinted 11p15 region. The possibility of common pathophysiological determinants has not been thoroughly investigated. Objective: To report abnormalities of the ploidy in two unrelated patients with congenital hyperinsulinism. Methods: Two patients with severe congenital hyperinsulinism, one overlapping with Beckwith-Wiedemann syndrome, had pancreatic histology, ex vivo potassium channel electrophysiological studies, and mutation detection of the encoding genes. The parental genetic contribution was explored using genome-wide polymorphism, fluorescent in situ hybridisation (FISH), and blood group typing studies. Results: Histological findings diverged from those described in focal congenital hyperinsulinism or Beckwith-Wiedemann syndrome. No potassium channel dysfunction and no mutation of its encoding genes ( SUR1, KIR6.2 ) were detected. In patient 1 with congenital hyperinsulinism and Beckwith-Wiedemann syndrome, paternal isodisomy for the whole haploid set was homogeneous in the pancreatic lesion, and mosaic in the leucocytes and skin fibroblasts (hemihypertrophic segment). Blood group typing confirmed the presence of two erythroid populations (bi-parental v paternal only contribution). Patient 2 had two pancreatic lesions, both revealing triploidy with paternal heterodisomy. Karyotype and FISH analyses done on the fibroblasts and leucocytes of both patients were unremarkable (diploidy). Conclusions: Diploid (biparental/paternal-only) mosaicism and diploid/triploid mosaicism were present in two distinct patients with congenital hyperinsulinism. These chromosomal abnormalities led to paternal disomy for the whole haploid set in pancreatic lesions (with isodisomy or heterodisomy), thereby extending the range and complexity of the mechanisms underlying congenital hyperinsulinism, associated or not with Beckwith-Wiedemann syndrome.